Tandem Mass Spectrometry Molecular Characterization - Varela Coelho, Ana; de Matos Ferraz Franco, Catarina (IntechOpen, 2013)
Tandem Mass Spectrometry - Molecular Characterization presents a comprehensive coverage of theory, instrumentation and description of experimental strategies and MS/MS data interpretation for the structural characterization of relevant molecular compounds. The areas covered include the analysis of drugs, metabolites, carbohydrates and protein post-translational modifications. The book series in Tandem Mass Spectrometry serves multiple groups of audiences; professional (academic and industry), graduate students and general readers interested in the use of modern mass spectrometry in solving critical questions of chemical and biological sciences.